HA Aktivitas Antimikroba dan Identifikasi Gen Penyandi Enterocins isolat Enterococcus faecalis K2B1 dari Susu Kerbau Belang Toraja: Antimikroba dan Gen Penyandi - Hasria Alang; Joni Kusnadi; Tri Ardyati; Suharjono (Universitas Muhammadiyah Prof. Dr. Hamka, 2020)
Background: Enterocin in Enterococcus is coded by enterocin encoding genes namely A, B, P and L50A / B. The purpose of this study was to identify enterocin gene encoding enterococcus faecalis K2B1 probiotic candidate from Belang Toraja buffalo milk and antimicrobial activity to S. typhi. Methods: identification of enterocin gene encoding using ent A, B, P and L50A / B, partial purification using ammonium sulfate on 80 % concentration and antimicrobial activity against to Salmonella typhi using disk diffusion method. The results of PCR amplification are then sequenced and BLASTX on NCBI. Result: Antimicrobial activity of Precipitate and crude against S. typhi are 193 and 201 respectively. Identification gene encoding enterocin shows that Ent A, B and P cannot be amplified and only EntL50A / B can be amplified with a sequence size of 86 bp. The sequence of enterocin encoding genes in E. faecalis K2B1 has 94% similarity with hypothetical protein EB34_00789 E. faecalis on GenBank with accession number RBR60004.1 Conclusion: EntL50A / B E. faecalis K2B1 has a size of 86 bp and is 94% identical to the hypothetical protein EB34_00789 and Enterocin can be used as antimicrobial or bio preservative.